Business Model Canvas: Bling Tracker / Muhammad Nur Aidil Ariff Muhamad Yusuf - Muhamad Yusuf, Muhammad Nur Aidil Ariff (2020)
Bling Tracker is a key chain that already modified with putting a tracker into it and one of the most backup devices that every person must have. The app can be found on Play Store for Android and App Store for IOS. Bluetooth are required to connect the app and tracker. When the consumer activate the app, the tracker will produce a loud sound. The uniqueness of Bling Tracker is the sound of tracker also can be selected. For the tracker, the battery are provided. If the battery cannot be used anymore, customer can change it by themselves because it is very easy. The use of retroreflective on the key chain to improve the visibility in low-lights surroundings and at night. Adding the GPS is a good alternative to help the customers to know where exactly the location of their belongings